Developing a Causal Model of Self-Directed Learning Based on Emotional Creativity with the Mediating Role of Knowledge Sharing and Information Literacy - Najafinia, Ali Akram; Jadidi, Hooshang; Zandi, Farzad (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to determine the goodness of fit of a causal model of self-directed learning based on emotional creativity with the mediating role of knowledge sharing and information literacy among graduate students. This descriptive correlational study was conducted on 215 graduate students enrolled at the University of Ilam during the 2022–2023 academic year, who were selected through random sampling. Data collection was carried out using the Fisher et al. Standard Self-Directed Learning Questionnaire, the Averill et al. Emotional Creativity Questionnaire, the Katz and Macklin Information and Communication Technology Literacy Questionnaire, and the Van den Hooff and Van Weenen Knowledge Sharing Questionnaire. Data analysis was performed using structural equation modeling (SEM) with Smart PLS software. The results indicated a positive and significant relationship between emotional creativity and information literacy. Additionally, a relationship was found between emotional creativity and knowledge-sharing behavior. Furthermore, there was a significant causal relationship between emotional creativity and self-directed learning, as well as between information literacy and self-directed learning. Based on the SEM results, the fit indices, including R², GOF, and Q², were satisfactory. Therefore, it can be concluded that the conceptual model of self-directed learning based on emotional creativity, with the mediating role of knowledge sharing and information literacy, aligns well with the empirical model.